2018
DOI: 10.1016/j.ygeno.2017.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA profiling reveals chi_circ_0008219 function as microRNA sponges in pre-ovulatory ovarian follicles of goats (Capra hircus)

Abstract: Circular RNAs (circRNAs) are a new class of non-coding RNAs in animals and are a novel target of non-coding RNA (ncRNA) regulation. The mechanism and function of circRNAs have been reported in some species and tissues. However, there is little available information on the functions of circRNAs in the goat reproductive system. In the present study, we deeply sequenced and analyzed circRNAs through bioinformatics to reveal the expression profiles, and predicted 13,950 circRNAs in the pre-ovulatory ovarian follic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
43
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 46 publications
2
43
1
Order By: Relevance
“…This would significantly reduce false positives of candidate circRNAs identified in GSF samples or OV samples. Furthermore, we found that > 98% of circRNAs were ecirRNAs, which differs from Hu's finding in which 86% of circRNAs were ciRNAs while only 13% were ecircRNAs and 1% were exon-intron circRNAs derived from the pre-ovulatory ovarian follicles of goats (Tao et al 2017). These discrepancies further demonstrate that the expression patterns of circRNAs are tissue specific and cell specific.…”
Section: Discussioncontrasting
confidence: 97%
“…This would significantly reduce false positives of candidate circRNAs identified in GSF samples or OV samples. Furthermore, we found that > 98% of circRNAs were ecirRNAs, which differs from Hu's finding in which 86% of circRNAs were ciRNAs while only 13% were ecircRNAs and 1% were exon-intron circRNAs derived from the pre-ovulatory ovarian follicles of goats (Tao et al 2017). These discrepancies further demonstrate that the expression patterns of circRNAs are tissue specific and cell specific.…”
Section: Discussioncontrasting
confidence: 97%
“…During the past few years, through high-throughput RNA sequencing and bioinformatics analysis, a great number of circRNAs have been discovered in different species and tissues. For example, 13,950 circRNAs were detected in pre-ovulatory ovarian follicles of goats, and 37 circRNAs were found to be differentially expressed 27 . Empirical Bayes sequencing analysis identified 11 down-regulated and 32 up-regulated circRNAs in embryos with black fur skin and white fur skin of mice, and these circRNAs may play a role in skin pigmentation 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, with the rapid development of bioinformatics techniques and deep sequencing, more functional circRNAs have been discovered in animal follicle development (Shen et al, 2019). Previous studies have shown that the circRNAs of follicles and GCs in goats, chicken, and humans were detected (J. Cheng et al, 2017; Shen et al, 2019; Tao et al, 2017). However, data associated with the function of circRNAs in ducks are still less reported, especially regarding follicle development.…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies have shown that the circRNAs of follicles and GCs in goats, chicken, and humans were detected (J. Cheng et al, 2017;Tao et al, 2017). However, data associated with the function of circRNAs in ducks are still less reported, especially regarding follicle development.…”
mentioning
confidence: 99%